Effects of active pharmaceutical ingredients mixtures in mussel Mytilus galloprovincialis - Gonzalez-Rey, Maria (2020)
Active pharmaceutical ingredients (APIs) are emergent environmental contaminants widely detected in surface waters as result of incomplete waste water treatment plant (WWTP) removal processes and improper disposal. The assessment of potential effects of APIs on non-target organisms is still scarce since besides presenting multiple chemical structures, properties and modes of action, these compounds occur as complex mixtures. This study comprises a 15-day exposure of mussels Mytilus galloprovincialis to mixtures (at environmentally relevant nominal concentrations) of non-steroidal inflammatory drugs ibuprofen (IBU) and diclofenac (DCF) (250 ng L(-1) each) and selective serotonin reuptake inhibitor (SSRI) fluoxetine (FLX) (75 ng L(-1)) (MIX 1) along with the addition of classical pro-oxidant copper (Cu) (5 μg L(-1)) (MIX 2). The goals included the assessment of oxidative stress, neurotoxic and endocrine effects on this sentinel species applying both a multibiomarker and gene expression (here and later gene expression is taken as synonym to gene transcription, although it is acknowledged that it is also affected by, e.g. translation, and mRNA and protein stability) analysis approaches. The results revealed a swifter antioxidant response in digestive glands than in gills induced by MIX 1, nevertheless the presence of Cu in MIX 2 promoted a higher lipid peroxidation (LPO) induction. Neither mixture altered acetylcholinesterase (AChE) activity, while both triggered the formation of vitellogenin-like proteins in females confirming the xenoestrogenic effect of mixtures. All these results varied with respect to those obtained in previous single exposure essays. Moreover, RT-PCR analysis revealed a catalase (CAT) and CYP4Y1 gene expression down- and upregulation, respectively, with no significant changes in mRNA levels of genes encoding superoxide dismutase (SOD) and glutathione-S-transferase (GST). Finally, this study highlights variable tissue and time-specific biomarker responses and gene expression alterations, which along with several interactions between each mixture component on each biomarker confirm the susceptibility of mussels to API mixtures.